2007
DOI: 10.1186/1471-2164-8-350
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium triggers an integrated reprogramming of the metabolism of Synechocystis PCC6803, under the control of the Slr1738 regulator

Abstract: Background: Cadmium is a persistent pollutant that threatens most biological organisms, including cyanobacteria that support a large part of the biosphere. Using a multifaceted approach, we have investigated the global responses to Cd and other relevant stresses (H 2 O 2 and Fe) in the model cyanobacterium Synechocystis PCC6803.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 65 publications
10
84
0
Order By: Relevance
“…In this study, DF/PF was shown to be the best phenomenological stress parameter: after only 5 h of exposure to DCMU and MV, a 50% reduction (compared to the control) was measured in the most intoxicated areas of leaves ( Figure 6). The effect of these chemicals is even more evident after 72 h. In addition, the effects of copper and cadmium significantly decreased the value of DF/PF at this time point, which is quite expected due to the wide spectrum of toxic action of the selected metals on the photosynthetic apparatus [29] and various metabolic processes [27,30].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, DF/PF was shown to be the best phenomenological stress parameter: after only 5 h of exposure to DCMU and MV, a 50% reduction (compared to the control) was measured in the most intoxicated areas of leaves ( Figure 6). The effect of these chemicals is even more evident after 72 h. In addition, the effects of copper and cadmium significantly decreased the value of DF/PF at this time point, which is quite expected due to the wide spectrum of toxic action of the selected metals on the photosynthetic apparatus [29] and various metabolic processes [27,30].…”
Section: Discussionmentioning
confidence: 93%
“…Cadmium interferes with the oxygen-evolving complex in PSII, the plastoquinone pool, and ribulose-1,5-bisphosphate carboxylase oxygenase (RubisCo) synthesis [28,29]. It is not a redox active-transition metal, but can indirectly expedite ROS production by substituting an essential micronutrient (e.g., disturbing Fe homeostasis; [30]) or binding non-specifically to thiol groups, thereby disturbing various metabolic processes [31].…”
Section: Introductionmentioning
confidence: 99%
“…WH7803, in much the same way as what has been observed in the freshwater Synechocystis sp. PCC 6803 in response to approximately millimolar H 2 O 2 concentrations (Li et al, 2004;Houot et al, 2007). Moreover, global transcriptomic data clearly indicated that H 2 O 2 and MV induced similar transcriptomic responses in both LL and HL Synechococcus sp.…”
Section: Transcriptome Response To Oxidative Stressmentioning
confidence: 91%
“…Accordingly, ftsH_1216, the ROS-induced direct ortholog of Synechocystis sp. PCC 6803 slr0228 gene (Li et al, 2004;Houot et al, 2007), encoding the FtsH2 protease involved in the clearance of damaged D1 proteins from inactivated PSII , belongs to the cluster of genes mainly activated in response to ROS in Synechococcus sp. WH7803 (cluster B; Fig.…”
Section: Transcriptome Response To Oxidative Stressmentioning
confidence: 99%
“…Aliquots of 200 ml of mid-log-phase cultures (2.5 ϫ 10 7 cells ml Ϫ1 ) were rapidly harvested by vacuum filtration (less than 1 min), resuspended in 4 ml of 50 mM Tris 50 (pH 8), 5 mM EDTA, immediately frozen in an Eaton press chamber cooled in a dry ice and ethanol bath, and disrupted (250 MPa). RNA was extracted and purified with the Qiagen RNeasy kit as we have previously described (18) and then treated with 20 U of DNase I, RNase-free (Applied Biosystems) for 30 min at 37°C. RNA concentration and purity (A 260 /A 280 ratio, Ͼ1.9) were determined with a Nanodrop apparatus (Thermo Scientific) and migration on an agarose gel to verify the absence of RNA degradation.…”
Section: Methodsmentioning
confidence: 99%